1996
DOI: 10.21273/hortsci.31.3.468
|View full text |Cite
|
Sign up to set email alerts
|

Foliar SPAD-502 Meter Values, Nitrogen Levels, and Extractable Chlorophyll for Red Maple Selections

Abstract: Twelve red maple selections in an existing field trial were evaluated for leaf chlorophyll content with a SPAD-502 chlorophyll meter, total foliar N concentration with a LECO CHN analyzer, and total foliar chlorophyll content (CHL) by N,N-dimethylformamide extraction. Selections included Acer rubrum L. `Autumn Flame', `Fairview Flame', `Franksred' (Red Sunset™), `Karpick', `Northwood', `October Glory', `Redskin', `Schlesin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(28 citation statements)
references
References 13 publications
1
27
0
Order By: Relevance
“…A largest percentage increase in the root/ shoot ratio in ZD958 (Table 1) Table S2). The SPAD value is positively correlated with the chlorophyll content in the leaf as a critical indicator of internal N nutritional status (Sibley et al 1996;Chapman and Baretto 1997). ZD958 had the lowest SPAD values in the 4th leaf among seven examined lines (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…A largest percentage increase in the root/ shoot ratio in ZD958 (Table 1) Table S2). The SPAD value is positively correlated with the chlorophyll content in the leaf as a critical indicator of internal N nutritional status (Sibley et al 1996;Chapman and Baretto 1997). ZD958 had the lowest SPAD values in the 4th leaf among seven examined lines (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…Neilsen et al (1995) observed significant correlations between CCI and foliar nitrogen concentration in four apple cultivars early, but not late, in the growing season. However, in a study that examined 12 red maple cultivars as a group, Sibley et al (1996) found no significant correlations between CCI and foliar nitrogen. These latter two studies illustrate some limitations of chlorophyll meters.…”
Section: Introductionmentioning
confidence: 91%
“…Significant correlations have been reported for CCI and total chlorophyll in paper birch (Betula papyrifera Marsh.) (Richardson et al, 2002), red maple (Acer rubrum L.) (Sibley et al, 1996) (Campbell et al, 1990). Cate and Perkins (2003) reported significant correlations between CCI and total chlorophyll in sugar maple (Acer saccharum Marsh.)…”
Section: Introductionmentioning
confidence: 99%
“…Compared to more expensive extraction methods, the SPAD meter can rapidly estimate chlorophyll content (Azia and Stewart 2001;Madeira et al 2003;Yamamoto et al 2002). In plant nutrition studies, the SPAD meter has been successfully used to estimate nitrogen status in apple (Neilsen et al 1995), tomato (Sandoval-Villa et al 2002, red maple (Sibley et al 1996), and corn (Smeal and Zhang 1994) among other crops (Schepers et al 1998). Loh et al (2002) used a SPAD meter to quantitatively evaluate Populus deltoides foliage quality and calibrated the instrument based on chlorophyll and nitrogen content.…”
Section: Introductionmentioning
confidence: 99%